النظام القانوني للجنة الدولية الإنسانية لتقصي الحقائق - إشوي عماد (مجلة الباحث في العلون القانونية والسياسية, 2019)
This paper attempts to investigate the legal system of the International Humanitarian Fact-Finding Commission (IHFFC). The research addresses the historical development of investigation, since 1899, till the enactment of the first additional protocol to the 1970 four Geneva conventions. The article 90 thereof institutes an independent and impartial commission charged with finding facts that fall within the ambit of the rules of the international humanitarian law between the States that accept the jurisdiction of the IFGGC. The research deals with the organization of the commission, namely the modes of designation of its members, their obligations, the election of its president and his/her deputies as well as his/her prerogatives. The competencies of the commission are brought to light, particularly investigation and good offices and, finally, the research tackles the task of evaluating the action of the commission.
Keywords: The International Humanitarian Fact-Finding Commission; legal system; investigation; good offices.